Do chão batido à sala de aula - a territorialização do MST na constituição da Escola Estadual de Ensino Fundamental Ataliba Rodrigues das Chagas - São Gabriel - Rio Grande do Sul - Horst, Karyn (2016)
In a time when the peoples of the field redefine the countryside of São Gabriel, a geographic look at the analysis of the MST territorialization in the constitution of the State Elementary School Ataliba Rodrigues das Chagas, located in the District of Batovi in the Municipality São Gabriel, in the state of Rio Grande do Sul, it should be released. The problem of the research lies in the study of how was the process of MST territorialization at the School Ataliba Rodrigues das Chagas, school that serves children from 7 MST settlements created in rural areas of San Gabriel, from the year 2008. Facing this question we can trace the general objective to grasp how was the process of reconfiguration of the State School Ataliba Rodrigues das Chagas, from the creation of settlements in São Gabriel, in 2008. Therefore it was necessary to: 1. conduct a historical review of the agrarian question in Brazil in order to understand the agrarian territorial development in San Gabriel, 2. compare the evolution of concepts of property and education in the various brasilians Constitutions, 3. address the struggle of the MST for land and especially the struggle of the MST for education in the municipality of São Gabriel, 4. understand how it was created the Educational Field legislation and how MST design education, 5. characterize the school studied and 6. understand what transformations of Ataliba School from the creation of settlements in São Gabriel, in the year 2008. To meet the goals formulated conducted a qualitative survey of bibliographic and documentary survey, questionnaires and interviews, and informal dialogues and making essays with school students. The process of the MST territorialization in the constitution of the State Elementary School Ataliba Rodrigues das Chagas began with the conquest of the land but needs to be constantly reflected and renewed for all segments that are part of the school community, as the people of the country no longer ag ree more to receive a school that does not effectively meet their interests.